Breast cancer radiology in women with hypothyroidism - S. K. Ternovoy; A. B. Abduraimov; K. A. Lesko (ABV-press, 2014)
The article describes the influence of hypothyroidism on the diagnostic efficacy of different breast imaging techniques. In 2010-2013 the study included 1008 patients: 501 (49.7 %) patients with hypothyroidism and 507 (50.3 %) patients without hypothyroidism.Mammography and ultrasound with Doppler mapping and qualitative elastography performed. Diagnostic effectiveness of mammography is lower in patients with hypothyroidism, than in patients without hypothyroidism. The combination of mammography and ultrasound with Dop- pler mapping is most effective in patients with hypothyroidism. Qualitative elastography is impractical because of the lack of additional infor- mation compared with Doppler.